(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The rapid expansion of digital communication technologies, social networking platforms, instant messaging applications, and virtual interactions has significantly transformed interpersonal and marital relationships in contemporary India. While technology has enhanced communication and connectivity, it has simultaneously created new forms of abuse, surveillance, emotional manipulation, and psychological violence within marital relationships. Digital harassment in marriage includes cyberstalking, online humiliation, unauthorized access to devices, monitoring of social media activities, circulation of private images, impersonation, threatening messages, excessive digital surveillance, and emotional blackmail through electronic means. These acts often lead to severe mental cruelty, emotional trauma, depression, anxiety, reputational harm, and marital breakdown. Indian matrimonial jurisprudence has gradually evolved to recognize mental cruelty as a valid ground for divorce under personal laws; however, the emergence of digital forms of cruelty has raised complex legal and evidentiary challenges. The concept of mental cruelty has undergone substantial judicial interpretation in India. Courts have expanded its meaning beyond physical violence to include emotional abuse, humiliation, neglect, false allegations, public defamation, and persistent psychological harassment. In the digital era, cruelty manifests through virtual means, making it difficult to establish evidence, identify intent, and balance privacy rights with matrimonial obligations. Digital abuse frequently intersects with cyber laws, data protection concerns, gender justice, domestic violence laws, and constitutional rights such as dignity, privacy, and freedom of expression. The Information Technology Act, 2000, the Bharatiya Nyaya Sanhita, 2023, the Protection of Women from Domestic Violence Act, 2005, and various matrimonial laws collectively provide partial remedies against digital abuse within marriage. Judicial decisions increasingly recognize online conduct, defamatory social media posts, invasive digital surveillance, and cyber harassment as factors constituting mental cruelty. However, the absence of specific legislative provisions addressing digital cruelty in marriage has resulted in fragmented legal responses. This article critically examines the emerging dimensions of digital harassment and mental cruelty in Indian marriages. It analyses the legal framework, judicial interpretations, constitutional perspectives, evidentiary challenges, gender dimensions, comparative international developments, and policy concerns. The study also explores the impact of artificial intelligence, deepfake technology, cyber monitoring applications, and digital evidence on matrimonial disputes. The article concludes that Indian family law must evolve to explicitly recognize technology-facilitated abuse within matrimonial relationships and provide effective legal remedies balancing privacy, dignity, and justice.